Impact of Clear Aligners on Oral Health and Oral Microbiome During Orthodontic Treatment - Maierdanjiang Rouzi; Xiaoqi Zhang; Qingsong Jiang; Hu Long; Wenli Lai; Xiaolong Li (Elsevier, 2023)
The demand for clear aligners has risen over the past decade because they satisfy patients' desire for less noticeable and more comfortable orthodontic appliances. Because clear aligners are increasingly used in orthodontics, there is a big push to learn more about the physiologic and microbial changes that occur during treatment. The present work highlighted further links between clear aligners and changes in oral health and the oral microbiome and provided plaque control methods for clear aligner trays. Existing literature revealed that clear aligners have no significant influence on the structure of the oral microbiome during orthodontic therapy. Clear aligner treatment demonstrated promising results in terms of controlling plaque index, gingival health, and the prevalence of white spot lesions. Nevertheless, grooves, ridges, microcracks, and abrasions on the aligner surface would provide a prime environment for bacterial adherence and the development of plaque biofilms. A combination of mechanical and chemical methods seems to be a successful approach for removing plaque biofilm from aligners whilst also preventing pigment adsorption.